A Novel Role of Connexin 40-Formed Channels in the Enhanced Efficacy of Photodynamic Therapy - Wu, Deng-Pan; Bai, Li-Ru; Lv, Yan-Fang; Zhou, Yan; Ding, Chun-Hui; Yang, Si-Man; Zhang, Fan; Wang, Yuan-Yuan; Huang, Jin-Lan; Yin, Xiao-Xing (Frontiers in Oncology, 2019)
Despite the responses of initial treatment of photodynamic therapy (PDT) are promising, the recurrence rate occurs. Thus, discovery of novel therapeutic targets to enhance PDT efficacy is an urgent need. Reports indicate that connexin (Cx) 40 plays an important role in tumor angiogenesis and growth. However, it is unknown whether Cx40-composed channels have effects on PDT efficacy. The study uniquely demonstrated that Cx40-formed channels could enhance the phototoxicity of PDT to malignant cells in vitro and in vivo. Specifically, Cx40-formed channels at high cell density could increase the PDT photocytotoxicity. This action was substantially prohibited when Cx40 expression was not induced or Cx40 channels were restrained. Additionally, the presence of Cx40-composed channels enhanced the phototoxicity of PDT in the tumor xenografts. The above results indicate that enhancing the function of Cx40-formed channels increases PDT efficacy. The enhancement of PDT efficacy mediated by Cx40 channels was related with intracellular pathways mediated by ROS and calcium pathways, but not lipid peroxide-mediated pathway. The work demonstrates the capacity of Cx40-mediated channels to increase PDT efficacy, and suggests that therapeutic strategies designed to maintain or enhance Cx40 expression and/or channels composed by Cx40 may increase the therapeutic efficacy of PDT.